All Days 2006
DOI: 10.2118/100508-ms
|View full text |Cite
|
Sign up to set email alerts
|

Downhole Scale Management in Gorm, Dan, and Halfdan, and Implications to Industry Trends

Abstract: TX 75083-3836, U.S.A., fax 01-972-952-9435. AbstractThree oil producing fields in the Danish sector of the North Sea, Gorm, Dan and Halfdan, have been assessed for downhole scale control. All three fields have water injection. To date downhole scaling has not been perceived as a significant production problem in these fields. This paper presents the results of a review of the well service history for each well in the three fields which identified when and where scales had been encountered and estimated the imp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…They found that the HCO − 3 concentration is approximately 400 mg/L for the Dan and Halfdan fields. [1] Hence, this value is used for reservoir conditions. (Also, we use the reservoir pressure reported here.…”
Section: Thermodynamic Modellingmentioning
confidence: 99%
See 4 more Smart Citations
“…They found that the HCO − 3 concentration is approximately 400 mg/L for the Dan and Halfdan fields. [1] Hence, this value is used for reservoir conditions. (Also, we use the reservoir pressure reported here.…”
Section: Thermodynamic Modellingmentioning
confidence: 99%
“…One which has higher pressure and temperature. [57] • Reservoir conditions (from [1]): − 17 000 kPa , 70 ∘ C, 400 mg/L HCO − 3 . Valdemar (from [57]): 37 000 kPa, 86 ∘ C, 400 mg/L HCO − 3 .…”
Section: ]) T H E a M B I E N T L E V E L O F Hco − 3 V A R I E S W I...mentioning
confidence: 99%
See 3 more Smart Citations